Burn after reading [videorecording (DVD)] - Coen, Ethan; Coen, Joel; Clooney, George; McDormand, Frances; Malkovich, John (Focus Features spotlight series, 2008)
Osbourne Cox is a CIA analyst who quits his job after being demoted. He decides to write a memoir about his life in the CIA. His wife, Katie, wants a divorce and, based on the advice of her divorce lawyer, she downloads many of his personal and financial files onto a disc. Katie's lover is Treasury agent Harry Pfarrer. The disc eventually finds its way to Hardbodies, a workout gym. An employee of the gym, Chad Feldheimer obtains the disc and ascertains that it contains classified government information. Along with his fellow employee, Linda Litzke, he intends to use the disc to blackmail Osbourne. When blackmailing him fails, Linda decides to take the information to the Russian embassy. At the embassy, she hands the disc over to the Russians, promising that she will give them more information. Linda and Chad don't have any more information, so they decide to break into Cox's house. This brings about a series of events that no one forsees.